Effect of particle and carbide grain sizes on a HVOAF WC-Co-Cr coating for the future application on internal surfaces: microstructure and wear - Pulsford, J.; Kamnis, S.; Murray, J.; Bai, M.; Hussain, Tanvir (Springer, 2017)
The use of nanoscale WC grain or finer feedstock particles are possible methods of improving the performance of WC-Co-Cr coatings. Finer powders are being pursued for the development of coating internal surfaces, as less thermal energy is required to melt the finer powder compared to coarse powders, permitting spraying at smaller stand - off distances. Three WC-0Co-4Cr coatings, with two different powder particle sizes and two different carbide grain sizes, were sprayed using a high velocity oxy-air fuel (HVOAF) thermal spray system developed by Castolin Eutectic - Monitor Coatings Ltd., UK. Powder and coating microstructures were characterised using XRD and SEM. Fracture toughness and dry sliding wear performance at three loads were investigated using a ball–on-disc tribometer with a WC–Co counter body. It was found that the finer powder produced the coating with the highest microhardness, but its fracture toughness was reduced due to increased decarburisation compared to the other powders. The sprayed nanostructured powder had the lowest microhardness and fracture toughness of all materials tested. Unlubricated sliding wear testing at the lowest load showed the nanostructured coating performed best; however at the highest load this coating showed the highest specific wear rates with the other two powders performing to a similar, better standard.